Monitoring and assessment in online collaborative environments [ emergent computational technologies for e-learning support - Juan, Angel A. , 1972- (Information Science Reference, 2010)
"The book provides researchers and developers of online collaborative systems with approaches for effective and efficient means that would assist e-learning students and teachers with precise and relevant information regarding the ongoing online learning activity at both individual and group levels"--Provided by publisher.